2017
DOI: 10.1121/1.5006903
|View full text |Cite
|
Sign up to set email alerts
|

Indoor noise annoyance due to 3–5 megawatt wind turbines—An exposure–response relationship

Abstract: The existing exposure–response relationships describing the association between wind turbine sound level and noise annoyance concern turbine sizes of 0.15–3.0 MW. The main purpose of this study was to determine a relationship concerning turbines with nominal power of 3–5 MW. A cross-sectional survey was conducted around three wind power areas in Finland. The survey involved all households within a 2 km distance from the nearest turbine. Altogether, 429 households out of 753 participated. The households were ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 34 publications
(68 reference statements)
0
5
0
Order By: Relevance
“…Epidemiological studies have consistently found that emission of noise from WTs is associated with annoyance (Guski et al. 2017; Hongisto et al. 2017; Michaud et al.…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies have consistently found that emission of noise from WTs is associated with annoyance (Guski et al. 2017; Hongisto et al. 2017; Michaud et al.…”
Section: Introductionmentioning
confidence: 99%
“…Second, larger WTs may emit more low-frequent sound [ 29 ]. However, changes in spectral shape are much less pronounced than in the situations studied here, and a recent study suggested that the size of WTs might not be relevant for annoyance [ 59 ]. Third, annoyance might be reduced by reducing the occurrence of periodic AM by blade pitch control [ 60 ] and by prevention of stall on the WT blades [ 14 ].…”
Section: Discussionmentioning
confidence: 86%
“…Similarly, indoor noise annoyance was systematically reduced with increasing distance from wind turbines. In the data provided by Hongisto, the rate of annoyed people was around 10% when within 1200 m of such noisy sources, becoming negligible when about 2 km away from the source [ 46 ]. Annoyance and sleep are also influenced by other factors.…”
Section: Resultsmentioning
confidence: 99%